Efficacy of modern fungicides against tomato alternaria blotch - Dzham, M.; Mykhailenko , S. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2020)
Goal. To determine the species composition of early blight on tomatoes and to establish the technical effectiveness of modern fungicides. Methods. The research was conducted in 2019—2020 in Cherkasy, PE «Poretsky» on tomatoes variety Zagadka. Weather conditions of the growing season favored the intensive disease development. Plot size — 10 m2 in 4 replicates, placement of plots — randomized. Agricultural techniques are common for the growing area. To determine the species composition of pathogens, during the growing season samples of plants with typical symptoms were taken. Isolation of phytopathogen in pure culture and their identification was carried out in the laboratory according to conventional methods. To determine the technical effectiveness of fungicides the following fungicides were used: Zorvek Incantia, SE (0.5 l/ ha), Orvego, KS (1.0 l/ha), Quadris 250 SC, hp (1.0 l/ha), Quadris Top 325 SC, KS (0.6 l/ha), Cabrio Duo, KE (2.5 l/ha), Signum, VG (0.3 kg/ha), Thanos 50, VG (1.0 kg/ha). Results. As a result of research, it was found that during the growing season early blight was the most common. According to our research, the disease is caused by two species of the pathogen Alternaria alternata (Fr.) Keissl. and Altrenaria solani Sorauer. We found that almost 70% of isolated and identified isolates were classified as Alternaria solani. For protecting of tomatoes against early blight following fungicides were used: Zorvek Inkantiya, CE (0,5 l/hectare), Orvego, KS (1,0 l/h), Kvadris 250 SC (1.0 l/ hectare ), Kvadris Top 325 SC (0.6 l/h), Kabrio Duo, KE (2.5 l/h), Signum, VG (0.3 kg/h), Tanos 50, VG (1.0 kg/h). Technical efficiency of them was 55.6—78.6%, and the stored harvest — 5.11—6.62 t/ha. Conclusions. As a result of researches we specified specific composition of early blight of tomatoes. It is set that disease is caused by two species: Alternaria alternata and Alternaria solani, that are different in anatomo-morphological properties. It is established that to protect tomatoes from Alternaria, it is advisable to apply the following fungicides: Kvadris 250 SC (1.0 l/h), Kvadris Top 325 SC (0.6 l/h), Kabrio Duo, KE (2.5 l/h).